2013
DOI: 10.1021/bi401343t
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proximal and Distal Axial Ligands in Leishmania major Pseudoperoxidase

Abstract: Previous optical and electron paramagnetic resonance (EPR) spectroscopic studies of the newly discovered peroxynitrite scavenging pseudoperoxidase from Leishmania major (LmPP) suggested that ferric LmPP contained a six-coordinate low-spin (6cLS) heme with a thiolate ligand, presumably a cysteine, bound to its heme iron. To identify the axial ligands of LmPP, we exploit a systematic mutational analysis of potential heme ligands. On the basis of UV-visible and EPR spectroscopy, we report that the substitution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Our crystal structure confirms previous work identifying the LmPP axial ligands using a combination of site-directed mutagenesis and UV/Vis spectrophotometry [19]. The heme is coordinated proximally by His 206 and distally by Cys 107 (Figure 2A).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our crystal structure confirms previous work identifying the LmPP axial ligands using a combination of site-directed mutagenesis and UV/Vis spectrophotometry [19]. The heme is coordinated proximally by His 206 and distally by Cys 107 (Figure 2A).…”
Section: Resultssupporting
confidence: 88%
“…UV/Vis spectroscopic studies also showed that the addition of PN causes a shift in the LmPP heme iron from ferric 6-coordinate low spin state to ferric high spin state in the absence of an electron donor. While mutagenesis studies point to His 206 and Cys 107 as the likely proximal and distal axial heme ligands, respectively [19], the absence of a crystal structure has been an obstacle to determining the mechanism of PN detoxification by LmPP. Here, we describe the 1.76-Å crystal structure of LmPP, in addition to kinetic and spectroscopic studies, in order to shed further light on the potential biological function of this intriguing heme protein.…”
Section: Introductionmentioning
confidence: 99%
“…The His/Cys − coordination found for Heme 1 in the TsdA enzymes is rare and, although the purpose of such ligation is not always clear (39), some examples are suggested to function as redox sensors (4042) and others as receptors or regulators (4347). Reported E m values lie in the range −350 to −160 mV (4043, 47).…”
Section: Discussionmentioning
confidence: 99%
“…3B suggest that the increased reduction product Cygb(Fe 2+ ) is likely caused by the increased A 2- concentration. It has demonstrated that increasing pH will stabilize the reduced state of the heme iron as shown in the case of alkaline cystathionine beta-synthase [35] and pseudoperoxidase from Leishmania major (LmPP) [36]. This stabilization may also contribute to the increase in the rate constant of Cygb(Fe 3+ ) reduction by Asc with increasing pH.…”
Section: Discussionmentioning
confidence: 99%